2014
DOI: 10.3171/2014.6.jns132038
|View full text |Cite
|
Sign up to set email alerts
|

Residual tumor volume and patient survival following reoperation for recurrent glioblastoma

Abstract: Object Maximal safe tumor resection is part of the standard of care for patients with newly diagnosed glioblastoma. The role of reoperation in the care of patients with recurrent glioblastoma is less clear, and less than a quarter of patients undergo a second surgery. Previous studies have identified preoperative variables associated with the improved survival of patients following reoperation, and guidelines for the selection of patients for reoperation have been devised and validated. In this study, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…Similarly, a prospective non-randomized registry for patients with repeat surgery identified a correlation between (high) extent of resection and survival [31].…”
Section: Surgery At Recurrencementioning
confidence: 94%
“…Similarly, a prospective non-randomized registry for patients with repeat surgery identified a correlation between (high) extent of resection and survival [31].…”
Section: Surgery At Recurrencementioning
confidence: 94%
“…Yong et al 22 confirmed the relevance of the extent of resection at reoperation after finding that a residual tumor volume of less than 3 cm 3 after reoperation exerted an impact on the patients' survival: OS values were 20 months in patients with TR, 11 months in patients with residual tumor volume less than 3 cm 3 and five months when the residual . Following a study with 170 patients, Oppenlander et al 23 concluded that an extent of resection larger than 80% in repeated surgery suffices to increase patients' survival.…”
Section: Extent Of Resection At Reoperationmentioning
confidence: 88%
“…The number of months between tumour removal and disease recurrence was, however, the independent variable most specifically related to OS (B = .313, t(42)= 3,213, p=.003) and was also related to post-operative KPS. This parameter summarizes the validity of the treatment and can be influenced by the presence of tumor residue [31] and resistance to treatment with temozolomide [20].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was performed by the same first operator with the aid of the following: neuronavigation system, intraoperative ultrasound, ultrasound aspirator (CUSA-CAVITRON), thulium laser and intraoperative neurophysiological monitoring. 19.40% of the procedures was conducted in awake surgery so as to monitor, real-time, the functions of the patient during surgery in eloquent areas. GTR was performed in 85.95% of cases, while STR in the residual 14.05%.…”
Section: Treatment Characteristicsmentioning
confidence: 99%